Islamic Derivatif - Sugeng Widodo (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2009)
In the early 1980s there was the discovery of new financial products to obtain high profits with a controlled risk called derivative transactions. Initially this transaction was intended as a tool to manage risk, but in its development it was more directed to speculation. Although conventional conception derivative transactions generally have shortcomings, they still have the potential for real benefits for the benefit of the people by redesigning a total innovative design to be an Islamic derivative transaction that brings benefits (eg, mutually beneficial to the perpetrators, efficient, avoiding risk) with eliminate mudharat (qimar, gharar, jahalah, istighlal). The design concept of conventional derivative transactions into Islamic derivative transactions can be explored using: Salam, Istihna ', Istijrar, Qardh, and Khiyar